Morphology of Carbon Nanotubes Using Thermal Chemical Vapor Deposition - Noppadon Sutthisiri,; Surasak Chiangga,; Ekachai Hoonnivathana,; Supreya Trivijitkasem,; Rachanee Rujiwarodom,; Apisit Songsasen,; Cherdsak Kunsombat, (Agriculture and Natural Resources, 2006)
A growth of carbon nanotubes (CNTs) on Ni-glass substrates at 700°C was achieved by thermal chemical vapor deposition (CVD) of acetylene gas. Acetylene gas was heated at 950°C, then flowed into area which was maintained at 700°C. The configuration and morphology of the CNTs was investigated using scanning electron microscope (SEM) and transmission electron microscope (TEM) which showed the bamboo-shaped CNTs and the curl-shaped CNTs with the diameter of 270 nm – 330 nm, and the length of 5-10 μm.